2007
DOI: 10.1196/annals.1381.014
|View full text |Cite
|
Sign up to set email alerts
|

Antipituitary Antibodies in Idiopathic Hyperprolactinemic Patients

Abstract: Hyperprolactinemia is often observed in lymphocytic hypophysitis (LYH). To clarify the possible autoimmune pituitary involvement in patients with apparently idiopathic hyperprolactinemia we investigated the presence of antipituitary antibodies (APA) in hyperprolactinemic patients with idiopathic hyperprolactinemia and in those with prolactinoma. Sixty-six hyperprolactinemic patients (52 F, 14 M age range 28-42 years, group 1) were studied. Of them, 34 out of 66 showed clinical features of hyperprolactinemia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 25 publications
2
17
0
1
Order By: Relevance
“…With regard to the persistence of clinical CDI for some months after delivery in both our cases, a particular role could have been played by PRL. In fact, it has been suggested that lactation and the related increased PRL levels may worsen some autoimmune diseases after delivery (28,29), given the well-known pivotal role played by PRL in the immune system (29). This may explain the prolonged persistence of CDI after delivery in our patients, considering that both cases experienced a normal and complete lactation accompanied by the physiological increase in PRL levels.…”
Section: Discussionsupporting
confidence: 50%
“…With regard to the persistence of clinical CDI for some months after delivery in both our cases, a particular role could have been played by PRL. In fact, it has been suggested that lactation and the related increased PRL levels may worsen some autoimmune diseases after delivery (28,29), given the well-known pivotal role played by PRL in the immune system (29). This may explain the prolonged persistence of CDI after delivery in our patients, considering that both cases experienced a normal and complete lactation accompanied by the physiological increase in PRL levels.…”
Section: Discussionsupporting
confidence: 50%
“…Because there are at least five types of cells in the pituitary gland, antibodies to different cell types, to different cell proteins or to different hormones may be the reason, and there are different techniques (like complement fixation, indirect immunoflorescence, immune blotting and enzyme-inked immunosorbent assay) to detect them. Autoantibodies to certain proteins may be positive in 70% of the patients [19] but they can be found in plasma of patients with other pituitary diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases this is due to very small microprolactinomas which cannot be seen on currently available imaging techniques [39]. Some research suggests that autoimmune pituitary involvement is responsible for idiopathic hyperprolactinemia, where high levels of antipituitary antibodies (25.7%) are found in these patients [40]. PRL levels are usually lower than 100 ng/mL [41].…”
Section: Causes Of Hyperprolactinemiamentioning
confidence: 99%